2017
DOI: 10.1021/jacs.6b13342
|View full text |Cite
|
Sign up to set email alerts
|

Surprisingly High Selectivity and High Affinity in Mercury Recognition by H-Bonded Cavity-Containing Aromatic Foldarands

Abstract: In the absence of macrocyclic ring constraints, few synthetic systems, possessing a mostly solvent-independent well-folded conformation that is predisposed for highly selective and high affinity recognition of metal ions, have been demonstrated. We report here such a unique class of conformationally robust modularly tunable folding molecules termed foldarands that can recognize Hg ions surprisingly well over 22 other metal ions. Despite the lack of sulfur atoms and having only oxygen-donor atoms in its structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 99 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…Interestingly, these acyclic foldamer molecules also exhibit good binding toward the K + ion. 5 Given the similarities in structure and in potassium binding between cyclic P5b and acyclic F1−F5, we believed F1−F5 might be capable of performing similar catalytic functions. We therefore decided to investigate the possible use of these acyclic foldamers to catalyze direct arylations of unactivated arenes with aryl halides in the absence of transition metals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, these acyclic foldamer molecules also exhibit good binding toward the K + ion. 5 Given the similarities in structure and in potassium binding between cyclic P5b and acyclic F1−F5, we believed F1−F5 might be capable of performing similar catalytic functions. We therefore decided to investigate the possible use of these acyclic foldamers to catalyze direct arylations of unactivated arenes with aryl halides in the absence of transition metals.…”
mentioning
confidence: 99%
“…We then further investigated the reactions using different bases (e.g., t-BuOLi, t-BuONa, and KOH) and found that no product could be obtained under the same conditions using F2 as the catalyst (entries 7−9, Table 1). Given the fact that F2 binds K + more strongly than Na + or Li + , 5 these results indicate that a stronger base (t-BuO − vs OH − ) and availability of such a base (e.g., t-BuO − ) in solution via potassium chelation by the ligand are critically important to drive the reaction to completion.…”
mentioning
confidence: 99%
“…The most commonly used donor atoms include N, S and O and the groups containing them involve (for N) azoic compound, amines, acidamide, azo groups or nitriles, (for S) thioalcohols, sulfoethers, or thiocarbamic acid esters, (for O) carboxyls, hydroxyls, phenols, ethers, carbonyls or phosphoryl groups. Previous studies have already illustrated the high speci city of phytate in sequestering Hg 2+ ions (De Stefano et al 2006), and the combination between carbonyls and Hg 2+ has high idiosyncrasy (Ermakova et al 2013, Shen et al 2017). In our study, despite the absorbent is nitrogen-and sulfur-free, the PA molecules provide su cient phosphoryl groups that can e ciently bind with Hg 2+ , even in the presence of some competing heavy metal ions (Mn 2+ , Cd 2+ , Cr 2+ , Cu 2+ and Pb 2+ ) (A/S ratio of 4.1 g L -1 ) (Table 3).…”
Section: Super-fast Regeneration Of the Absorbentmentioning
confidence: 99%
“…The large library of structural motifs of foldamers enables the design of countless functions and applications [ 174 , 175 , 176 ], including sensing [ 151 , 177 ]. Thanks to the structural control of foldamers, they can be designed to bind complementary guests [ 178 ], e.g., cations [ 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 ], anions [ 186 , 187 , 188 , 189 , 190 , 191 , 192 ], or non-charged molecules [ 164 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 ]. They have been applied in the detection of metal ions [ 210 , 211 , 212 , 213 ], explosives [ 214 ], biomarkers [ 215 ], pH [ 216 , 217 ], membrane curvature [ 218 ], and fructose [ 198 ] ( Table 3 ).…”
Section: Foldamers In Sensingmentioning
confidence: 99%